dy/dt = ky(1-y)
seperation of variables
(1/y*(1-y)) dy = k dt
integrate
-ln ((y-1)/y) + c = kt +c
move c's to right side and apply both sides as power of e
(y/(y-1)) = e ^ (kt +c)
drop down c since e ^ (kt +c) = c*e ^ (kt)
(y/(y-1)) = c*e ^ (kt)
Uh, well, not sure where to go with solving here but it ends up as
y = (c*e ^ (kt)) / (c*e ^ (kt) - 1)
Good ol' TI-89...Sorry I wasn't really sure where to go with the solving for y. Maybe you can see it... Also, did it have an inital condition?
Haha, never mind, ok, here we go, figured it out:
y / (y - 1) = e ^ (kt + c)
multiply by y-1
y = (y - 1)*e ^ (kt + c)
distribute
y = y*e^(kt + c) - e ^ (kt + c)
move y*e^(kt + c) to left
y - y*e ^ (kt + c) = -e ^ (kt + c)
factor out y on left side
y (e ^ (kt + c) - 1) = e ^ (kt + c)
divide (e ^ (kt + c) - 1) to move to right side
y = e ^ (kt + c) / (e ^ (kt + c) - 1)
Yay!
2006-12-23 12:46:53
·
answer #1
·
answered by Mike J 3
·
0⤊
0⤋
This is separable. Dividing through, we get dy/y(1-y) = kdt. Integrating both sides, Log[y/y-1] = kt+C. So, solving for y, we get
y = Ce^kt / (Ce^kt-1). Note that y=0 and y=1 are also solutions.
Steve
2006-12-23 20:43:25
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
dy/dt=ky(1-y)
by solving the eqn, (1-y)dy=kydt
divide through by y (1/y-1)dy=kdt
Intergrate both sides with respect to y and t
==> lny-y=kt
==> lny-y-kt=0 Is the general solution
2006-12-23 21:00:10
·
answer #3
·
answered by jodesy 1
·
0⤊
2⤋
Definition: y=t^a dy/dt=at^(a-1)
Step 1. a=k
Step 2. (a-1)=(1-y)
Step 3. t=y
Substitute 1 & 2, (k-1)=(1-y)
Answer, y=t
2006-12-23 20:57:59
·
answer #4
·
answered by bunywars5000 3
·
0⤊
2⤋